Peran Badan Permusyawaratan Desa dalam Mengawasi Penyelenggaraan Pemerintahan di Desa Berdasarkan Undang-Undang Nomor 6 Tahun 2014 Tentang Desa (Studi pada Desa Sabah Balau Kec. Tanjung Bintang Lampung Selatan) - S. Endang Prasetyawati (Universitas Bandar Lampung (UBL), 2016)
The village is a unit of community that has boundaries. Authorized to regulate and manage the affairs of government, local community interests and customary rights recognized and respected in the government system. Supervising the implementation of the village administration is the most important reason why the Village Consultative Body (BPD) to be formed. The problem in this research is, how the role of the Village Consultative Body (BPD) in overseeing governance at village method used is, juridical normative and empirical approaches. Data collection procedures consist of literature studies and field studies. The analysis used is qualitative analysis. The results of the research, that the role of the Village Consultative Body (BPD) in overseeing governance in rural Sabah Balau, are in accordance with Act No. 6 of 2014 concerning the village. But not maximum, low participation of rural communities in helping BPD supervision as well as delays in the provision of operational funds BPD in their duties, become an obstacle BPD in monitoring the fullest. The advice given is, should the Village Consultative Body (BPD) Sabah Balau can further maximize its performance in monitoring governance in the village. And the village government should be more transparent in organizing the village administration.